The Comparison of Analogue Pain Scale, Quadriceps Muscle, and Knee Joint among Obese Women with Knee Osteoarthritis - Nur Azis Rohmansyah; Syahruddin; Wulan Rahmadhani; Ashira Hiruntrakul (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
Introduction: Patients with knee osteoarthritis were reported to have quadriceps weakness and impaired knee function, related to pain. It is unclear whether body composition is a causal factor to the above findings. Aim: The purpose of this study was to investigate differences in pain, quadricep strength, and knee function among obese women and women of normal weight with knee osteoarthritis. Methods: Fifty women with a mean age of 55 years were involved in this study. The inclusion criteria were bilateral knee of knee osteoarthritis with a visual analogue pain scale difference (>1) between each knee. Patients all underwent assessment of the pain intensity, isokinetic strength of knee muscles, and knee function. Results: The analysis showed that there were significant differences between groups in pain intensity (p=0.004) and quadriceps strength (p=0.003) but were not significant on the Lequesne index score (p=0.05). Significant differences in the intensity of knee pain and quadriceps strength occurred between the obesity II group with the normal weight group (p=0.004), overweight (p=0.017) and with obesity I (p=0.017) suffering from knee osteoarthritis. Conclusion: Normal weight people with knee osteoarthritis are at risk of suffering knee pain that causes reduced physical activity. This inactive condition will also result in a decrease in quadriceps muscle strength, which can increase the risk of knee deformity. Therefore, proper education and training programmes are required to anticipate this, so as to prevent the progression of knee osteoarthritis.